The Shadow Economy – the Polish Perspective - Grzegorz Gołębiowski (Contemporary Economics, 2007)
The article deals with the phenomenon of the so called "grey", "shadow" or "twilight" economy, which has been assessed here as a function of a given mix of economic policies. This key concept is first defined, then analyzed through the prism of its driving/growth factors. The analysis contains quantitative data illustrating the scale of such factors in Poland (alongside international comparisons). Having catalogued the principal reasons for the prevalence of îshadow economicsî, the article endeavors to demonstrate the ramifications of economic activity being undertaken in the îtwilight zoneî. Such ramifications are likely to be of a positive and negative nature, however, the latter tend to be - by far - more striking. The phenomenon has been viewed against a backdrop of the Polish economic framework, notably symptoms of over-regulation vis-à-vis the general business environment, with particular references to over-fiscals. The analysis formulates policy orientated conclusions relating to specific areas where reform need be initiated/advanced as well asdirections for further research findings in respect of the "shadow economy".